1911 N.J. Laws 185 - (:unkn) unknown (My University, 1911)
Ch. 128, 1: It shall be unlawful to use any silencer, when hunting for game or fowl, on any gun, rifle or firearm, under a penalty of twenty dollars for each offense.
Keywords: HUNTING REGULATION; SUPPRESSORS